2004
DOI: 10.17487/rfc3933
|View full text |Cite
|
Sign up to set email alerts
|

A Model for IETF Process Experiments

Abstract: The IETF has designed process changes over the last ten years in one of two ways: announcement by the IESG, sometimes based on informal agreements with limited community involvement and awareness, and formal use of the same mechanism used for protocol specification. The first mechanism has often proven to be too lightweight, the second too heavyweight.This document specifies a middle-ground approach to the system of making changes to IETF process, one that relies heavily on a "propose and carry out an experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Following a community discussion, it was concluded that [RFC3933] is not an appropriate framework for this experiment, primarily because no change is required to any existing process.…”
Section: Process Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a community discussion, it was concluded that [RFC3933] is not an appropriate framework for this experiment, primarily because no change is required to any existing process.…”
Section: Process Experimentsmentioning
confidence: 99%
“…The process in this document is offered as an experiment (though not as an [RFC3933] experiment; see Section 5). Authors of Internet-Drafts are encouraged to consider using the process for their documents, and working groups are invited to think about applying the process to all of their protocol specifications.…”
Section: Introductionmentioning
confidence: 99%
“…RFC 4693 [RFC4693] established the IETF Operational Notes (IONs) series of documents on the experimental basis [RFC3933]. This series was intended to discuss the set of procedures that the IETF follows, but for which the RFC publication process is an inappropriate documentation vehicle.…”
Section: Moving Rfc 4693 To Historic Statusmentioning
confidence: 99%
“…Per RFC 3933 [RFC3933], in March 2008, the IESG decided to terminate the IONs process experiment [IESG-IONS]. This document moves RFC 4693 to Historic status, per [HISTORIC], to reflect experiment closure.…”
Section: Moving Rfc 4693 To Historic Statusmentioning
confidence: 99%
“…The document series is a process experiment according to RFC 3933 [RFC3933]. The properties list does not include a "category"; while the set of documents that might be IONs is extremely wide, we do not know yet which categories could make sense.…”
mentioning
confidence: 99%